Durability of wood treated with propolis - Akcay, Caglar; Birinci, Emre; Birinci, Ceren; Kolayli, Sevgi (BioResources, 2020)
Propolis is an important antifungal agent found naturally in beehives and used as a food supplement for many purposes. This study aimed to use methanolic propolis extract (MPE) as a treatment material as an antifungal agent for wood preservation. Scots pine and paulownia woods were exposed to Trametes versicolor and Neolentinus lepideus fungi for 12 weeks, and untreated woods were used as the controls. Compared with the control, paulownia wood exposed to N. lepideus had a 47.2% mean mass loss, while the treated wood with 7% MPE had an 11.6% mean mass loss. In addition, a 27.2% mass loss occurred with the control for Scots pine when exposed to N. lepideus, and a 2.5% mass loss occurred with the 7% propolis-treated specimens. Total phenolic content and the phenolic profile of the raw propolis samples were also analyzed. Scanning electron microscopy images showed that the propolis extracts still remained in the wood cells without being degraded after the fungal destruction and the propolis-treated specimens were more durable against fungal decay compared to the untreated control specimens. The results from this study indicated that propolis could be used as an environmentally compatible and natural wood preservative to protect wood against fungal attack.
Keywords: White-Rot Fungi; Argentina; Impregnation; Decay fungi; Wood; Propolis; Degradation; Chemical-Characterization; Antifungal Activity; Inhibition; 15. Life on land